2002
DOI: 10.1039/b111645b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, and reactions of a nitroxyl complex of iridium(iii), cis,trans-IrHCl2(NHO)(PPh3)2

Abstract: Reaction of Ir(NO)(PPh3)3 with anhydrous HCl results in addition of 2 equivalents of HCl with formal protonation of the nitrosyl ligand, affording the unusual six-co-ordinate nitroxyl complex cis,trans-IrHCl2(NH=O)(PPh3)2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 16 publications
3
32
0
1
Order By: Relevance
“…The marked drop in t NO from that of free HNO [32] at 1563 cm À1 is suggestive of the HNO ligand in [Ru(ttp)(HNO)(1-MeIm)] behaving as a strong p-acid. Hillhouse and coworkers [23,31] have previously documented the p-acidity of the HNO ligand in coordination complexes, and we have shown that the related nitrosoarenes (ArNO) are p-acids in [M II (por)(ArNO)]-containing complexes (M ¼ Fe, Ru, Os) [19]. To date, there are four X-ray structural reports of metal-HNO complexes; three of these reveal Nbinding of the HNO ligand attached to the metal (for Os, Ir, Ru) [28,30,31], and one reveals a side-on g 2 binding of the HNO ligand in a Mo complex [33].…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The marked drop in t NO from that of free HNO [32] at 1563 cm À1 is suggestive of the HNO ligand in [Ru(ttp)(HNO)(1-MeIm)] behaving as a strong p-acid. Hillhouse and coworkers [23,31] have previously documented the p-acidity of the HNO ligand in coordination complexes, and we have shown that the related nitrosoarenes (ArNO) are p-acids in [M II (por)(ArNO)]-containing complexes (M ¼ Fe, Ru, Os) [19]. To date, there are four X-ray structural reports of metal-HNO complexes; three of these reveal Nbinding of the HNO ligand attached to the metal (for Os, Ir, Ru) [28,30,31], and one reveals a side-on g 2 binding of the HNO ligand in a Mo complex [33].…”
mentioning
confidence: 98%
“…Hillhouse and coworkers [23,31] have previously documented the p-acidity of the HNO ligand in coordination complexes, and we have shown that the related nitrosoarenes (ArNO) are p-acids in [M II (por)(ArNO)]-containing complexes (M ¼ Fe, Ru, Os) [19]. To date, there are four X-ray structural reports of metal-HNO complexes; three of these reveal Nbinding of the HNO ligand attached to the metal (for Os, Ir, Ru) [28,30,31], and one reveals a side-on g 2 binding of the HNO ligand in a Mo complex [33]. The t NO value of 1380 cm À1 in [Ru(ttp)(HNO)(1-MeIm)] suggests that the HNO ligand is N-bound to the Ru center, as this value is similar to the 1306-1332 cm À1 values observed in the related compounds [Ru(por)-(ArNO)(L)] (L ¼ pyridine, 1-MeIm) with N-bound nitrosoarene ligands [34,35].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The complex IrHCl 2 (HNO)(PPh 3 ) 2 , previously described by Roper, was recently structurally characterized by Hillhouse and coworkers [129]. The iridium atom is in a pseudo-octahedral environment possessing cis chlorides and trans phosphine ligands.…”
Section: (Nhoh)(no)(pph 3 ) 2 [125]mentioning
confidence: 99%
“…Indeed, interconversion of these partially reduced nitrogenous species, including their organic derivatives such as nitrosoalkanes (RNO), on late transition-metal centers remains unexplored [3][4][5][6][7][8] compared with that on the early transition metals. [9,10] In an early example, Roper and coworkers [3] reported the reversible protonation of the nitrosyl complex [Ir(NO){P(C 6 H 5 ) 3 [4] the second protonation site of the nitroxyl complex, for example, is still unclear. We now describe the stepwise transformation of nitrosylruthenium complexes to nitrosoalkane and N-alkylhydroxylamido(1À) complexes, as well as the facile interconversion of the latter two species.…”
mentioning
confidence: 99%